2004
DOI: 10.1203/01.pdr.0000128980.82797.29
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation Effect on Surfactant Content, Function, and Lung Compliance in the Newborn Rat

Abstract: Studies of ventilator-associated lung injury in adult experimental animal models have documented that high tidal volume (TV) results in lung injury characterized by impaired compliance and dysfunctional surfactant. Yet, there is evidence that, in neonates, ventilation with a higher than physiologic TV leads to improved lung compliance. The purpose of our study was to evaluate how lung compliance and surfactant was altered by high TV ventilation in the neonate. We utilized a new model (mechanically air-ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
(29 reference statements)
2
20
1
Order By: Relevance
“…For this reason, no blood gases and pH were obtained in the experimental and control animal. In previously published work, we have demonstrated that in newborn rats these ventilator settings result in normal blood pH at the end of 60 min ventilation (16). Yet, the experimental animals' gas exchange status may have differed from our own published data because of meconium-induced ventilation-perfusion mismatch.…”
Section: Animalscontrasting
confidence: 50%
See 2 more Smart Citations
“…For this reason, no blood gases and pH were obtained in the experimental and control animal. In previously published work, we have demonstrated that in newborn rats these ventilator settings result in normal blood pH at the end of 60 min ventilation (16). Yet, the experimental animals' gas exchange status may have differed from our own published data because of meconium-induced ventilation-perfusion mismatch.…”
Section: Animalscontrasting
confidence: 50%
“…Newborn animals were mechanically ventilated as previously described (16). Briefly, the animals were sedated with an intraperitoneal injection of a mixture of xylazine and ketamine (8 and 80 mg/kg, respectively).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Verbrugge et al 25 found that significant changes in surfactant composition and function occurred after application of high V T on top of ZEEP, and setting an adequate PEEP prevented surfactant dysfunction. Martinez et al 12 using a neonatal rat model pointed at stretch-induced surfactant release to explain improved lung compliance after ventilation with extreme V T of 40 mL/kg and ZEEP.…”
Section: Discussionmentioning
confidence: 99%
“…9 In terms of lung development and alveolarization 2 week old rats correspond to 1-2 year old human infants. 10,11 Ventilator-associated lung injury (VALI) has been studied in infant rats with healthy lungs 7,8,12 or after lipopolysaccharide exposure 13 using V T ventilation ranging from 25 to 40 mL/kg and 0 cmH 2 O PEEP. However, it is not clear how infant rats respond to high but less extreme lung stretch over a longer period of time when compared to low V T ventilation with high PEEP.…”
Section: Introductionmentioning
confidence: 99%